My Vision of Terroir - Kehler, Mateo (Cuizine, 2010)
This short essay explores the possibility of nurturing a notion of terroir in Vermont. In the classical sense terroir is the expression of an economy rooted in a landscape (not imposed on a landscape). But how does a dynamic relationship between economy and landscape get created when the political economy of food and agriculture in the United States has consistently moved away from any connection to place? The possibilities of having independent Yankee farmers move towards terroir is explored.